Peraturan Kepala Daerah Yang Diterbitkan Tanpa Dasar Hukum - Herman, Hendra; Widowaty, Yeni (Universitas Widya Gama Malang, 2024)
This writing aims to examine the existence of Regional Head Regulations according to the hierarchy of laws and regulations in Indonesia and to find out how the force of law binds the material content of Regional Head Regulations which were formed without a legal basis. The research method used in this writing is normative legal research using a statutory approach. The results of the study show that regional head regulations are delegated legislation whose existence can only be recognized if ordered by higher laws and regulations and based on authority so that the contents of regional head regulations cannot conflict with the main regulations and/or regulations above them. The contents of the Regional Head Regulations that have been promulgated in regional news have binding legal force in general and must be obeyed by the public. Content material for Regional Head Regulations whose formation is not in accordance with statutory regulations may be subject to judicial review to the Supreme Court.